(untitled) (Scientific journal of the Fergana State University, 2023)
The article defines the concept of phraseological equivalence, and also examines the differences between full phraseological equivalents and partial ones. The semantic and structural features of English and Russian phraseological equivalents that describe the appearance of a person are also considered, and an etymological description of some Russian and English phraseological units is given